Intrascleral neurilemmoma. Issue 5 (May 1989) - Graham, C M; McCartney, A C; Buckley, R J
Abstract : The case of an anteriorly situated, intrascleral, neurilemmoma in an 11-year-old girl is reported. Only two similar cases have been described in the literature, and the diagnosis was made only after detailed histological examination, including electron microscopy and specialised staining techniques, to differentiate a neurilemmoma (schwannoma) from a neurofibroma.